The Relationship between Mother's Role as Educator and Early Childhood Knowledge about Sex in the Working Area of Puskesmas Batu Bandung, Kepahiang Regency, 2023 - Febriyanti, Febriyanti; Samidah, Ida; Iswari, Indra (Student Scientific Journal, 2024)
Sex education is still very taboo and is still considered not a topic of conversation that needs to be discussed with children. talk about sex is not an easy conversation for parents. Parents tend to avoid and close themselves about this topic by prohibiting children from asking and talking about sex. Based on the facts in the field, the level of sexual violence against children continues to increase every year. The purpose of this study was to identify the relationship between the role of mothers as educators with early childhood knowledge about sex in the working area of Puskesmas Batu Bandung in 2023.This type of research is analytical observational with cross sectional design. The number of samples of this study were 92 respondents selected by putposive sampling technique. The instrument used was a questionnaire. Data were analyzed using the chi-square test. The results showed that most of the respondents (72.8%) stated that their mothers acted as educators in early sex education, half of the respondents had good knowledge about early sex. The results of the Chi-Square test obtained p = 0.000 means that there is a relationship between the role of mothers as educators with early childhood knowledge about early childhood sex. This research should be used as information and reference material to examine how the role of parents in early childhood sex education.